Hustle and gig struggling and surviving in the sharing economy - Ravenelle, Alexandrea J., 1980- (University of California Press, 2019)
"The sharing economy claims to bring the romance of entrepreneurship to the masses. Through qualitative interviews with nearly eighty workers for Airbnb, Uber, TaskRabbit, and Kitchensurfing, 'Hustle and Gig' explores how the gig economy's classification of workers as "independent contractors" results in a shifting of risk and liability as part of a larger casualization of labor. Just like their colleagues in the 1800s and early 1900s, workers find themselves outside even the most basic workplace protections regarding discrimination and sexual harassment, the right to unionize, and redress for workplace injuries. The sharing economy is a movement forward to the past as it upends generations of workplace protections in the name of disruption"--Provided by publisher.